Ethnocultural Empathy of Adolescent from the Four Major Tribes in Indonesia - Tri Sutanti; Agungbudiprabowo Agungbudiprabowo; Ariadi Nugraha; Dian Ari Widyastuti (Universitas Ahmad Dahlan, 2022)
This study aimed to determine the level of ethnocultural empathy among adolescents from the four major ethnic groups in Indonesia. Participants were thirty-two adolescents studying in the guidance and counseling study program at Ahmad Dahlan University, Yogyakarta, recruited using a purposive sampling technique. They were Javanese, Sundanese, Malay, and Lampung. Data were collected using an ethnocultural empathy scale and analyzed descriptively. Taking a closer look at each component, participants exhibit the highest score in acceptance of cultural differences. Javanese, Malay, and Lampung participants exhibited the lowest emphatic awareness, while Sundanese participants showed the lowest emphatic feeling expression. The result of this study could be taken into account when developing counseling strategies to develop adolescents’ empathy at the university level adapted to the characteristics of their ethnic background.